El aprendizaje y sus incidencias en las actividades intraclase de los estudiantes de noveno año de Educación Básica del Instituto Tecnológico Dr. José Ochoa León Mera del cantón Pasaje, período lectivo 2013-2014 - González González, Luis David (2014)
Traditional education has focused its learning axis on the memorization of contents, however, modern pedagogy has not been unaware of this fact and has raised new ways to improve the construction of knowledge. One of those parameters that have been strengthened are intraclses activities, because it enhances meaningful learning, but-essentially-this didactic action that the teacher applies is aimed at the student to develop his / her critical thinking capacity and his / her own way of learning.